Cloud Cluster - Thakur, Mr Roshan; Khadatkar, Avinash; Kulkarni, Ajinkya; Giradkar, Chinmay; Humne, Vicky (IJRDO -Journal of Computer Science Engineering, 2015)
Cloud computing refers tothe delivery of computing resourcesover the Internet. Without storing thedata on the external hard drive orupdating applications for yourneeds. Cloud computing involvesdeploying groups of remote serversand software networks that allowcentralized data storage and onlineaccess to computer services orresources. Cloud service includesstorage of online file, webmail, andonline business applications. Cloudcomputing is a pool of sharedresources, which includes space fordata storage, efficient computerprocessing and specialized corporateand user applications. This paperintroduces a technique to provide anapplication which can be deployedinto the cloud to access the data online. To achieve this we are usingcloud as “Software as a Service”(SaaS).